Natalizumab-induced POU2AF1/Spi-B upregulation: A possible route for PML development. Issue 3 (June 2016) - Meira, Maria; Sievers, Claudia; Hoffmann, Francine; Haghikia, Aiden; Rasenack, Maria; Décard, Bernhard F.; Kuhle, Jens; Derfuss, Tobias; Kappos, Ludwig; Lindberg, Raija L.P.
Abstract : Objectives: To assess messenger RNA (mRNA) expression of POU2AF1 and Spi-B and their potential regulatory microRNAs (miRNAs) in natalizumab-treated patients with multiple sclerosis and in therapy-associated progressive multifocal leukoencephalopathy (PML). Methods: Expression of POU2AF1/Spi-B was analyzed by using real-time reverse transcription PCR assays on isolated B/CD8 + T lymphocytes and peripheral blood mononuclear cells (PBMCs) from cohorts of untreated and natalizumab-treated patients with and without PML. Longitudinal expression analysis was performed on CD4 +, CD8 + T and B cells from 14 patients who interrupted natalizumab therapy for 8 weeks. The miRNA profiling was conducted in PBMCs from 5 untreated and 5 natalizumab-treated patients using low-density arrays followed by validation with single miRNAs assays in untreated and natalizumab-treated patients. Results: POU2AF1 and Spi-B mRNAs were upregulated in B and CD8 + T cells from natalizumab-treated patients, which was validated in PBMCs from different cohorts of natalizumab-treated patients with and without PML, with a noteworthy higher expression of Spi-B in patients with PML. In contrast, downregulation of POU2AF1/Spi-B expression was measured in B and CD8 + T cells after natalizumab discontinuation. Seventeen differentially expressed miRNAs including miR-10b, a regulator of POU2AF1 mRNA, were identified in long-term natalizumab-treated patients compared with untreated ones. Conclusions: Upregulation of POU2AF1 and Spi-B, known transactivators of the JC virus, the causative agent for PML, and its association with occurrence of PML in natalizumab-treated patients, corroborates POU2AF1/Spi-B as potential biomarkers for PML risk, which merits further evaluation.